The Impact of Undergraduate Program Developers and User Participation on the Quality of School Information System - Nur W. Rahayu; Novi Setiani; Hanson P. Putro; Irena Yolanita Maureen (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Developer's expertise and user participation are two critical factors of successful School Information System (SIS). Many researchers focus on user-initiated and professional SIS, while this study observes a campus-initiated SIS which involves undergraduate developers and volunteer users. We qualify the system using the System Usability Scale (SUS) and observation. The final prototype reaches an acceptable level of SUS and the outcomes among students whose GPA above 3.0 are not much different, but we recommend to find students with good grades in the supporting courses. The volunteer users come from 2 public and two private schools in Yogyakarta, Indonesia. We also examined user participation and found they were good and even excellent, although each developer may have a different standard of perceiving user participation. This study also reveals user inconsistency and interface issues were still become problematic, as changes cause the project to be overdue.